The Effect of Rice Crop Production and Farmer Exchange Rate on Farmers' Income In Medan Krio Village - Anggia Ramadhan (Universitas 17 Agustus 1945 Semarang, 2023)
The research was conducted in Medan Krio Village, Sunggal District, Deli Serdang Regency, North Sumatra Province. The purpose of this study was to analyze the variables of crop production and the exchange rate of farmers to the income of rice farmers in Medan Krio Village both partially and simultaneously. The research data used are primary. In addition, secondary data is also used as support for primary data. The data analysis technique used is a direct interview of respondents with the help of a questionnaire that has been prepared. The data analysis method used is Multiple Linear Regression. The results of this study variable crop production have a significant effect on the income of rice farmers in Medan Krio Village. And the variable exchange rate of farmers has an insignificant effect on the income of rice farmers in Medan Krio Village. The simultaneous variables of crop production and farmer exchange rates simultaneously do not affect the income of farmers in Medan Krio Village. The suggestion in the research is that there is a need for intervention from the government and the private sector to increase farmers' crop production to improve the welfare of farmers.